Analisis Pengaruh Kualitas Produk dan Citra Merek terhadap Loyalitas Pelanggan pada Produk Skintific yang Dimediasi Kepuasan Pelanggan - Pingkan Viola Martiza; Sri Murwanti (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This study aimed to analyze the effect of product quality and brand image on customer loyalty, which is mediated by the customer satisfaction variable for Skintific products in Solo Raya. The type of research used is quantitative research, which distributes questionnaires via Google Forms. The population of this study was all people who live in Solo Raya. The sample used in this study was 150 respondents with the criteria for female community respondents who have used Skintific products. The sampling technique in this study used non-probability sampling techniques and purposive sampling. The data was analyzed using SmartPLS 3.0. The results of this study show that product quality significantly affects Skintific Product Customer Satisfaction in Soloraya. Brand Image has a significant effect on Employee Performance. Customer Satisfaction has a positive impact on Skintific Product Customer Loyalty in Soloraya. Product quality positively affects skintific product customer loyalty, which is mediated by customer satisfaction. Brand Image positively affects Customer Loyalty for skintific products mediated by Customer Satisfaction.